Pediatric Patient With Concurrent Eosinophilic Esophagitis, Erosive Reflux Esophagitis, and Barrett's Esophagus - Sharma, Ishna (ACG Case Rep J, 2020)
Eosinophilic esophagitis and Barrett's esophagus are believed to be separate disease processes, with erosive esophagitis leading to Barrett's esophagus. We report a rare case of concurrent diagnoses in a pediatric patient and examine the relevant genetic profiles in the esophagus.